Effectiveness of BPMC Application against Bemisia tabaci (Gennadius) Population and CMMV Disease Incidence on Soybean - Wartono Wartono; I Wayan Laba; Wawan Wawan (Jurnal Entomologi Indonesia, 2011)
Control of whitefly (Bemisia tabaci (Gennadius)) is the starting point in suppressing the CMMV disease (cowpea mild mottle virus). This study aims to determine the influence of applications BPMC (500 g a.i./l) against B. tabaci populations and disease incidence of CMMV on soybean plants. Research was conducted in the field with randomized complete block design consisting of 5 treatments i.e. five concentration levels: 0.75, 1.50,2.25, and 3.00 ml/l including control (untreated) with 5 replications. The results showed that BPMC is effective in suppressing the adult population of B. tabaci and disease incidence of CMMV.